Sintesis Biooil dari Limbah Pelepah Kelapa Sawit Berbasis Metode Pirolisis - Hendra Saputra; Ahdiat Leksi Siregar; Rahma Yusni Oktavia; Dimas Frananta Simatupang (REACTOR: Journal of Research on Chemistry and Engineering, 2023)
Biooil is a liquid obtained from cracking lignocellulose structures into simpler compounds from the pyrolysis process. The lignocellulose content in palm midrib can be used as a raw material for making biooil. This study examines the effect of the length of time burning at a temperature of 250 ℃ on the physical and chemical characteristics of the resulting biooil. The independent variable was pyrolysis time with 1 hour, 2 hours, and 3 hours. The parameters used to determine the quality of biooil are specific gravity, pH, color, and composition of biooil by GC-MS instrument. From the results obtained, the highest yield of biooil was 7.9945% from sample with 2 hours pyrolysis time. The quality of biooil showed the average pH ranged between 2.65–3.08 and the average density ranged from 1.0485 to 1.1055. The visual of biooil was dark brown color with the largest biooil content being Cis-Vaccenic acid.